Candida lipolytica UCP0988 Biosurfactant: Potential as a Bioremediation Agent and in Formulating a Commercial Related Product - Santos, Danyelle K. F.; Resende, Ana H. M.; de Almeida, Darne G.; Soares da Silva, Rita de Cássia F.; Rufino, Raquel D.; Luna, Juliana M.; Banat, Ibrahim M.; Sarubbo, Leonie A. (Frontiers in Microbiology, 2017)
The aim of the present study was to investigate the potential application of the biosurfactant from Candida lipolytica grown in low-cost substrates, which has previously been produced and characterised under optimised conditions as an adjunct material to enhance the remediation processes of hydrophobic pollutants and heavy metals generated by the oil industry and propose the formulation of a safe and stable remediation agent. In tests carried out with seawater, the crude biosurfactant demonstrated 80% oil spreading efficiency. The dispersion rate was 50% for the biosurfactant at a concentration twice that of the CMC. The biosurfactant removed 70% of motor oil from contaminated cotton cloth in detergency tests. The crude biosurfactant also removed 30 to 40% of Cu and Pb from standard sand, while the isolated biosurfactant removed approximately 30% of the heavy metals. The conductivity of solutions containing Cd and Pb was sharply reduced after biosurfactants’ addition. A product was prepared through adding 0.2% potassium sorbate as preservative and tested over 120 days. The formulated biosurfactant was analysed for emulsification and surface tension under different pH values, temperatures and salt concentrations and tested for toxicity against the fish Poecilia vivipara. The results showed that the formulation had no toxicity and did not cause significant changes in the tensoactive capacity of the biomolecule while maintaining activity demonstrating suitability for potential future commercial product formulation.